Pengembangan UMKM Pesona Plastic melalui Produk Desain dari Limbah Plastik dengan Pemanfaatan Teknologi dan Strategi Manajemen Bisnis Berkelanjutan - Suryani, Ni Kadek; Prasiani, Ni Komang; Dewi, Ni Made Emmi Nutrisia; Lestari, Ni Putu Emilika Budi; Utami, Sri; Artana, I Wayan Bimaskaran; Utama, Giovanni Rachmat (Prima Abdika: Jurnal Pengabdian Masyarakat, 2023)
The development of Micro, Small, and Medium Enterprises in Pesona Plastic, Batubulan Village, Gianyar Regency, Bali, focuses on the development of design products that use plastic waste as raw material. This effort involves the utilization of technology and sustainable business management strategies. The methods used include training and mentoring. This article outlines concrete steps in the development of Pesona Plastic UMKM, including the plastic waste processing process, the development of innovative design products, and the implementation of sustainable business management strategies. Activities conducted include the procurement of equipment and various training sessions, such as product design training for accessories and fashion, website integration training, interior product design training, digital marketing training, packaging design training, entrepreneurship and financial management training for UMKM and youth, social media marketing training, layout design, and space organization training, as well as equipment usage workshops. The results are successful efforts to reduce the impact of plastic waste, create high-quality products, and improve the well-being of the Pesona Plastic UMKM community in Batubulan Village. The follow-up plan for this program involves collaboration between IDB Bali and Pesona Plastic UMKM, with future involvement of students for practical training and the realization of designed products that serve a useful purpose.